Critical Synthesis Package: University of Iowa OSCE Standardized Patient Communication Checklist - Karla Hemesath (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) A Critical Analysis of the psychometric properties and the application to health science education of the University of Iowa OSCE Standardized Patient Communication Checklist; (2) a copy of the University of Iowa OSCE Standardized Patient Communication Checklist and psychometric data developed by George Bergus, MD. The University of Iowa OSCE Standardized Patient Communication Checklist is a 15 item measure used by standardized patients (SPs) to assess medical student communication skills during OSCEs. The current version groups items into four domains: Eliciting Information, Nonverbal, Patient Education, and Global Assessment. The global assessment domain includes an additional item requesting open-ended SP feedback on the student's performance. The checklist was developed for use alongside checklists specific to clerkship content in formative OSCEs in clerkships. While the clinical content of each OSCE varies, the communication skills expected are the same and are assessed through use of this checklist. To complete the checklist, respondents indicate the frequency of which they observed the communication behavior (not done, once, occasionally, frequently, throughout) with the exception of items 1 and 14 which are each scored as yes or no. The communication skills checklist may also be used by trained lay assessors in an outpatient pediatric setting to assess student communication skills while conducting patient encounters. Results of generalizability studies indicate that aggregation of scores throughout a clinical year into a score set may be used to reliably identify students with performance issues. A limiting factor in the use of the measure is the lack of instructions for SP use. An additional limitation of the instrument is the lack of quantification of the response choices. It is not clear from the materials submitted and the published studies how the choices are quantified and standardized across raters. This impacts the psychometric properties of the instrument.